Artefact-centric business process configuration. (2016) - Kang, Guosheng; Yang, Liqin; Xu, Wei; Tian, Zhaoyang; Zhang, Liang
Currently, there are two mainstream process modelling paradigms: the traditional activity-centric approach and the recent artefact-centric approach. Several approaches have been proposed for configuration of traditional activity-centric business processes; however, to the best of our knowledge, few approaches have been developed for artefact-centric business processes. This paper fills this gap by proposing a novel configuration approach for artefact-centric business processes. The configuration of artefact-centric process modelling is achieved by the configuration of artefact lifecycle models for all the involved artefact classes. First, we apply deterministic finite automaton to formalise an artefact lifecycle model (ALM). To derive configurable ALM, we propose merger operation for ALMs. Also, an artefact lifecycle graph (ALG) is proposed to describe ALM as a state diagram, and the structural soundness of ALG is also presented. Then, we propose configurable artefact lifecycle graph (C-ALG) to describe the configurable artefact lifecycle model, in which arcs and sets of business rules can be defined to be configurable points. Finally, by configuring C-ALGs for each artefact class with our individualisation algorithm, structurally sound artefact lifecycle models are derived (including data models of artefacts, associated services and business rules), thus resulting a complete configured artefact-centric process model.